2014
DOI: 10.1002/jat.3012
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro estrogenic activities of triclosan and triclocarban

Abstract: Triclosan (TCS) and triclocarban (TCC), as broad spectrum antibacterial agents, are distributed widely in the environment and humans. Most studies have focused on their distribution and biodegradation, but the endocrine-disrupting effects of these chemicals, especially their estrogenic effects, are still unclear. In the present study, we investigated the estrogenic effects of TCS and TCC using a series of in vitro assays, including the ER reporter gene assay in the CV-1 cells, E-screen assay and evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 50 publications
4
52
2
2
Order By: Relevance
“…On the other hand, triclosan is flagged as suspicious by our models and should, thus, be prioritized for further experimental testing. In this respect, recent mounting scientific evidence documents its adverse health effects: endocrine disruption, skin irritation and bacterial and antibiotic resistance [54].…”
Section: Predictions Of Ten Representative Estrogenic Substances and Ofmentioning
confidence: 99%
“…On the other hand, triclosan is flagged as suspicious by our models and should, thus, be prioritized for further experimental testing. In this respect, recent mounting scientific evidence documents its adverse health effects: endocrine disruption, skin irritation and bacterial and antibiotic resistance [54].…”
Section: Predictions Of Ten Representative Estrogenic Substances and Ofmentioning
confidence: 99%
“…TCS is a type of weak estrogen that affects classical estrogen nuclear receptors (ERα and ERβ) (Gee et al, 2010;Huang et al, 2014). However, the present study demonstrated that TCS's estrogen activity results from its effects on GPER, a novel membrane receptor, rather than its effects on the classical ERα and ERβ receptors.…”
Section: Discussionmentioning
confidence: 49%
“…TCS has adverse effects on biological growth and development such as influencing reproduction and endocrine disorders. Many previous studies document the acute or long-term exposure toxicity of TCS to various organisms, such as fish, invertebrates and amphibians (Huang et al, 2014). For example, Yueh and Tukey (2016) found that long-term TCS exposure led to liver tumors and produced oxidative stress in mice.…”
Section: Introductionmentioning
confidence: 99%
“…It is structurally homologous to BPA [47], and experimental evidence in vitro indicates estrogenic, anti-estrogenic, and anti-androgenic activities [48,49], however not necessarily confirmed in vivo [46]. Still, experimental data reported a higher rate of implantation failures among mice treated with high doses of triclosan [50].…”
Section: Environmental Phenolsmentioning
confidence: 83%